820. Impact of pulsed xenon ultraviolet (PX-UV) light disinfection for reduction of pathogens on high touch surfaces following hospitalization. (31st December 2020) - Jarrah, Joud N; Martinez, Oscar I; jain, Susmita; Chatterjee, Piyali; Choi, Hosoon; Hwang, Munok; Bennett, Morgan; Martel, JulieAnn; Xi, Jing; Stibich, Mark; Kaye, Keith S; Jinadatha, Chetan; et al.
Abstract: Background: Ultraviolet (UV) light disinfection following a manual terminal cleaning process for hospital rooms has been proposed as an additional method to reduce the bacterial burden on surfaces. The impact of UV light disinfection and the level of interdependence between the modalities remains unclear. Methods: Samples were collected from 5 high touch surfaces from 10 patients room following discharge prior to manual disinfection, following manual disinfection, and following pulsed xenon UV disinfection using Rodac contact plates (total 150 samples). Colonies were identified using MALDI-TOF mass spectrometry. The bacterial colony counts were recorded and analyzed as pathogenic or commensal organisms (based on CDC criteria) to assess the efficacy of the disinfection process. Results: Average colony counts for the rooms prior to disinfection, post disinfection, and post UV light were 185.8 CFU +/- SD 280, 43 CFU +/- 121, and 20 CFU +/- 36.7 respectively. The average drop in colony-forming units of the five high touch areas in patient's rooms can be seen in table 1. Twelve commensal bacterial species were isolated: Bacillus species (sp.), Corynebacterium sp., Enhydrobacter sp., Kocuria sp., Lysinibacillus sp., Macrococcus sp., Micrococcus sp., Paenibacillus sp., Pantoea sp., Psychrobacter sp., Siccibacter sp., Coagulase negative staphylococcus . Seven pathogenic bacteria were isolated: Acinetobacter sp., Brucella sp., Proteus sp., Staphylococcus aureus, Escherichia sp., Enterococcus, and Pseudomonas aeruginosa. Reductions in the predominant bacterial species following disinfection modality are noted in table 2. Table 1: Colony forming units (CFUs) average Pre-disinfection (Pre-Dis), Post Disinfection (Post-Dis), and Post PX-UV Light (PX-UV). Table 2: Sub-analysis of commensal and pathogen isolation Pre-Disinfection (Pre-Dis), Post-Disinfection (Post-Dis), and Post PX-UV light (PX-UV). Conclusion: A combination of manual disinfection and UV has shown a notable additional reduction in overall bacterial contamination of the patient rooms, including the majority of high touch areas as compared with manual disinfection alone. No additional reduction in commensal bacteria isolates was noted after UV light, however a further decrease in pathogenic bacteria (Acinetobacter and Enterococcus ) was noted. UV light may be considered as an additional room disinfection method to reduce overall bacterial burden and pathogenic bacterial contamination of rooms as a comprehensive strategy to reduce nosocomial infections. Disclosures: Mark Stibich, n/a, Xenex Germ-Zapping Robots (Board Member, Grant/Research Support) Chetan Jinadatha, MD, MPH, AHRQ (Research Grant or Support)Department of Veterans Affairs (Other Financial or Material Support, Owner: Department of Veterans Affairs. Licensed to: Xenex Disinfection System, San Antonio, TX)Inventor (Other Financial or Material Support, Methods for organizing the disinfection of one or more items contaminated with biological agents)NiH/NINR (Research Grant or Support)NSF (Research Grant or Support)Xenex Healthcare Services (Research Grant or Support)